Turkey's contribution to international policing - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
The UN Department of Peacekeeping Operations has undergone significant changes in its organisation since 1948. A new global environment established by the end of Cold War, elevated the Police Division to a more pronounced role in international peace as an essential pillar of UN peacekeeping missions. Nonetheless, despite the increased role of police in international missions, research on police contributions to peacekeeping remains limited. This article addresses this gap in literature by highlighting the case of Turkey's contribution to UN international police peacekeeping missions. The article confirms empirically that the Turkish police contribution has increased since the 2000s by relying on quantitative data offered by the TUBAKOV dataset designed to collect data on international peacekeeping missions of Turkey. The paper contends that, besides global trends, the increased participation of Turkey in UN-led missions reflects its internal political dynamics. First, under the JDP rule, Turkey's Cold War era subtle foreign policy was transformed to a proactive policy in global politics. Second, since the 2000s, the transformation of civil-military relations has ended the system of military tutelage, and this has had a considerable impact on foreign policy. Civilian authority, by abolishing military dominance, has become the primary actor in foreign policy decision-making.
Keywords: Police; UN; peacekeeping; Turkey; international policing; middle powers; CIVIL-MILITARY RELATIONS; SECURITY; TRANSFORMATION